2018
DOI: 10.1071/wf17150
|View full text |Cite
|
Sign up to set email alerts
|

The wildfire within: gender, leadership and wildland fire culture

Abstract: This article examines findings from a 2016 study on gender and leadership within the British Columbia Wildfire Service (BCWS), Canada. The study utilised action research to facilitate an in-depth conversation among wildland firefighters about gender and leadership, and to explore participant-derived actions steps within the BCWS towards a perceived ideal future(s). The study found widespread occurrences of gender discrimination in the day-to-day practice of leadership, and that gender made a difference for wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In 2016, Eriksen et al (2016) considered the issue of gender difference in mentoring, training, and leadership [64]. In 2018, Reimer and Eriksen [65] unraveled the links of gender, leadership, and wildland fire culture, by providing clear insights into gender discrimination into leaderships, and highlighted the trade-off between gender diversity and excellence among research participants. In 2018, in her book 'Gender and Wildfire Landscapes of Uncertainty', Christine Eriksen examined wildfire awareness and preparedness amongst women, men, households, communities, and agencies, at the interface between the city and beyond.…”
Section: Gender Equality and Climate-based Hazardsmentioning
confidence: 99%
“…In 2016, Eriksen et al (2016) considered the issue of gender difference in mentoring, training, and leadership [64]. In 2018, Reimer and Eriksen [65] unraveled the links of gender, leadership, and wildland fire culture, by providing clear insights into gender discrimination into leaderships, and highlighted the trade-off between gender diversity and excellence among research participants. In 2018, in her book 'Gender and Wildfire Landscapes of Uncertainty', Christine Eriksen examined wildfire awareness and preparedness amongst women, men, households, communities, and agencies, at the interface between the city and beyond.…”
Section: Gender Equality and Climate-based Hazardsmentioning
confidence: 99%
“…Gender is no longer understood as a characteristic determined by biological sex. The creation of binaries between male/female, man/woman, and femininity/masculinity as opposite and fixed “two‐category demographic variable[s]” (Pacholok, , p. 31) limits our understanding of how gender functions in social interactions (Reimer, ). Currently, gender is “widely conceptualized as a socially constructed relationship” (Pacholok, p. 28), which means that it is fluid, created through relationship with others, and not specifically linked to biological sex.…”
Section: Constructions Of Gendermentioning
confidence: 99%
“…Although little research can be found to explain the more nuanced experiences of male leaders practicing feminine leadership in male‐dominated industries, males’ expression of more feminine characteristics may cause negative effects in the context of majority male peer groups (hooks, ; Katz, ). As such, valuing the feminine as weak does a disservice to both men and women, as it limits our ability to choose to express ourselves in ways that are fully self‐actualized, thereby giving ourselves and others in the social group the ability to access the full spectrum of qualities—both masculine and feminine (Reimer, ). However, males inherently benefit from invisible privileges (Connell & Messerschmidt, ; Katz, ; Kimmel, ; McIntosh, ) associated with hegemonic patriarchal structures.…”
Section: Problematizing the Notion Of Feminine Leadershipmentioning
confidence: 99%
“…, 2014, p. 909; Reimer and Eriksen, 2018, p. 716). For example, looking at gender we can see that there is a majority of men in disaster management; with a feminist perspective we understand that there is also a hegemonic masculinity which actively exclude anyone who does not match this specific form of masculinity (Eriksen, 2013; Reimer and Eriksen, 2018) [2]. Feminist theories and methodologies then give ways to center the experiences of minorities.…”
Section: Introductionmentioning
confidence: 97%
“…Those researches often argue that a feminist perspective is necessary to reveal the power relations and inequalities connected to gender and give more visibility to women and gender minorities (Dominey-Howes et al. , 2014, p. 909; Reimer and Eriksen, 2018, p. 716). For example, looking at gender we can see that there is a majority of men in disaster management; with a feminist perspective we understand that there is also a hegemonic masculinity which actively exclude anyone who does not match this specific form of masculinity (Eriksen, 2013; Reimer and Eriksen, 2018) [2].…”
Section: Introductionmentioning
confidence: 99%